2022
DOI: 10.1093/jmammal/gyac079
|View full text |Cite
|
Sign up to set email alerts
|

Forest disturbance and occupancy patterns of American ermine (Mustela richardsonii) and long-tailed weasel (Neogale frenata): results from a large-scale natural experiment in Maine, United States

Abstract: Weasels are small mustelid carnivores that play an important role as predators of small mammals in a wide array of ecosystems. However, their response to land use, such as forest harvest for timber products, is seldom the subject of focused research and management projects. Both the American ermine, also known as the short-tailed weasel (Mustela richardsonii), and the long-tailed weasel (Neogale frenata) are native to Maine, United States, where commercial timber harvesting is widespread. The effects of this f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 58 publications
2
7
0
Order By: Relevance
“…In their review of mammal responses to boreal forest disturbance, Fisher and Wilkinson (2005) noted a lack of information regarding mesocarnivore relationships with disturbance. Recent studies concurrent with our work on red foxes found that the intensity of forest disturbance had a negative effect on American marten ( M. americana ) and fisher ( Pekania pennanti ; Evans & Mortelliti, 2022a), but a positive effect on weasels (Evans & Mortelliti, 2022b). Previous research has found that red foxes occur more in forested areas, especially those 20–30 years post clear cut, compared with regenerating (<5 years post clear cut) or uncut stands (Forsey & Baggs, 2001; Thompson, 1988).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In their review of mammal responses to boreal forest disturbance, Fisher and Wilkinson (2005) noted a lack of information regarding mesocarnivore relationships with disturbance. Recent studies concurrent with our work on red foxes found that the intensity of forest disturbance had a negative effect on American marten ( M. americana ) and fisher ( Pekania pennanti ; Evans & Mortelliti, 2022a), but a positive effect on weasels (Evans & Mortelliti, 2022b). Previous research has found that red foxes occur more in forested areas, especially those 20–30 years post clear cut, compared with regenerating (<5 years post clear cut) or uncut stands (Forsey & Baggs, 2001; Thompson, 1988).…”
Section: Discussionsupporting
confidence: 77%
“…Thick dark lines are model-predicted means and thin colored lines are a subset of model predictions from the Markov chain Monte Carlo simulations to depict uncertainty. Evans & Mortelliti, 2022a), but a positive effect on weasels (Evans & Mortelliti, 2022b). Previous research has found that red foxes occur more in forested areas, especially those 20-30 years post clear cut, compared with regenerating (<5 years post clear cut) or uncut stands (Forsey & Baggs, 2001;Thompson, 1988).…”
Section: Discussionmentioning
confidence: 90%
“…in forest cover, consistent with our ndings here(Sleeter et al 2013;Sohl et al 2016). While few studies have examined the habitat needs of North American weasels, American ermine have a noted association with forests, though use of grassland, shrubland, meadows has also been recorded(Lisgo 1999;Linnell et al 2017;Evans and Mortelliti 2022). We also noted forest cover positively in uenced suitability for this species, and regions (e.g., Northeast) that gained forest cover showed corresponding increased suitability while areas that lost forest cover (e.g., Rocky Mountain and Paci c Northwest;Sleeter et al 2013, Sohl et al 2016 showed similar declines in the area of predicted suitability.While American ermine appears to be associated at broad scales with forested landscapes, least weasels tend to avoid forest cover at landscape scales(Zub et al 2008).…”
supporting
confidence: 85%
“…While some studies have suggested a positive association with forested environments, grasslands, or edge habitats (Polder 1968; She eld and Thomas 1997), Gehring et al (2021) noted habitat selection of long-tailed weasels does not differ from the assumption of random use at landscape scales. Likewise, Evans and Mortelliti (2022) found no relationship between forest cover and long-tailed weasel occupancy, suggesting reported variability in habitat associations for this species may be due to their large geographic distribution. We also found that neither forest cover, nor any other land cover class was a strong predictor of suitable conditions for long-tailed weasels.…”
Section: Discussionmentioning
confidence: 69%
“…The spatial and temporal patterns of human land‐use have complex effects on ecosystems, from the fragmentation of habitat to changes in species composition, and different species respond differently over time since disturbance (Fischer and Lindenmayer 2006, Evans and Mortelliti 2022 a , b ). In the short‐term, the immediate effects of human disturbance and habitat alteration can have acutely negative effects on black bears, such as direct mortality (e.g., road kill) and abandonment of home ranges or den sites leading to cub death (Elowe and Dodge 1989).…”
Section: Discussionmentioning
confidence: 99%